Analisis Sektor Ekonomi Unggulan Di Kabupaten Tuban Provinsi Jawa Timur Tahun 2017-2021 - Wahyu Tri Widya Astuti; Wahyu Hidayat Riyanto (Program Studi Ekonomi Pembangunan, 2022)
The sustainable economic growth of a region is the main thing that is important for the development of regional economic growth itself. The main objective of this study is to analyze the leading sectors of the economy of Tuban Regency as a material for consideration of economic development planning. The data analysis tools used in this research are Static Location Quotient (SLQ) and Dynamic Location Quotient (DLQ) analysis, Shift Share analysis, and Klassen Typology with the research period 2017-2021 using GRDP of Tuban Regency and GRDP of East Java Province. The results of the LQ analysis, Shift Share analysis, Klassen typology analysis show that there is only one leading sector, namely the mining and quarrying sector because it is included in the criteria for the leading sector, showing a positive value which means the sector has a competitive advantage and has high competitiveness and the sector is fast progressing and fast growing.